2022
DOI: 10.7150/thno.65948
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 induces podocyte injury and proteinuria by activating β-catenin signaling

Abstract: Background: C-X-C chemokine receptor type 4 (CXCR4) plays a crucial role in mediating podocyte dysfunction, proteinuria and glomerulosclerosis. However, the underlying mechanism remains poorly understood. Here we studied the role of β-catenin in mediating CXCR4-triggered podocyte injury. Methods: Mouse models of proteinuric kidney diseases were used to assess CXCR4 and β-catenin expression. We utilized cultured podocytes and glomeruli to delineate the signal pathways involved. Conditional knockout mice with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
(76 reference statements)
1
11
0
Order By: Relevance
“…This cascade of phosphorylation of signalling proteins is also consistent with our previous findings in other classic CKD models. 21,22 Meanwhile, CXCR4 triggered renal tubular cell senescence, renal fibrotic lesions and FAO deficiency (Figures 2, 5 and 6). Knockdown of CXCR4 in ADR mice model ameliorated renal injuries, and inhibited β-catenin (Figure 3), preserved mitochondrial function and retarded cellular senescence (Figure 4).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This cascade of phosphorylation of signalling proteins is also consistent with our previous findings in other classic CKD models. 21,22 Meanwhile, CXCR4 triggered renal tubular cell senescence, renal fibrotic lesions and FAO deficiency (Figures 2, 5 and 6). Knockdown of CXCR4 in ADR mice model ameliorated renal injuries, and inhibited β-catenin (Figure 3), preserved mitochondrial function and retarded cellular senescence (Figure 4).…”
Section: Discussionmentioning
confidence: 97%
“…[17][18][19][20] Our previous studies also found that CXCR4 promotes tubular cell injury and renal fibrosis via activating β-catenin signalling. [21][22][23] Wnt/β-catenin signalling is an evolutionarily conserved pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Paraffin-embedded mouse and human kidney sections (3 μm thickness) were prepared by a routine procedure (48,49). The sections were stained with Sirius red staining or Masson's trichrome staining, according to the manufacturer's protocols, respectively.…”
Section: Histology Immunohistochemical and Immunofluorescence Stainingmentioning
confidence: 99%
“…Formalin-xed Para n-embedded mouse kidney sections (4 µm) were prepared, dewaxed, washed in down-graded alcohols and water by a routine procedure. Hematoxylin-eosin (HE) staining and Masson's trichrome staining (MTS) were performed using routine protocol (21). For immunohistochemical staining, depara nized sections were incubated with 3% H2O2 solution to inhibit endogenous peroxidase activity.…”
Section: Histology and Immunohistochemical Stainingmentioning
confidence: 99%